SARS-CoV-2 Spike Protein Induces Degradation of Junctional Proteins That Maintain Endothelial Barrier Integrity - Raghavan, Somasundaram; Kenchappa, Divya Borsandra; Leo, M. Dennis (Frontiers in Cardiovascular Medicine, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) uses the Angiotensin converting enzyme 2 (ACE-2) receptor present on the cell surface to enter cells. ACE-2 is present in many cell types including endothelial cells, where it functions to protect against oxidative damage. There is growing evidence to suggest that COVID-19 patients exhibit a wide range of post-recovery symptoms and shows signs related to cardiovascular and specifically, endothelial damage. We hypothesized that these vascular symptoms might be associated with disrupted endothelial barrier integrity. This was investigated this in vitro using endothelial cell culture and recombinant SARS-CoV-2 spike protein S1 Receptor-Binding Domain (Spike). Mouse brain microvascular endothelial cells from normal (C57BL/6 mice) and diabetic (db/db) mice were used. An endothelial transwell permeability assay revealed increased permeability in diabetic cells as well as after Spike treatment. The expression of VE-Cadherin, an endothelial adherens junction protein, JAM-A, a tight junctional protein, Connexin-43, a gap junctional protein and PECAM-1, were all decreased significantly after Spike treatment in control and to a greater extent, in diabetic cells. In control cells, Spike treatment increased association of endothelial junctional proteins with Rab5a, a mediator of the endocytic trafficking compartment. In cerebral arteries isolated from control and diabetic animals, Spike protein had a greater effect in downregulating expression of endothelial junctional proteins in arteries from diabetic animals than from control animals. In conclusion, these experiments reveal that Spike-induced degradation of endothelial junctional proteins affects endothelial barrier function and is the likely cause of vascular damage observed in COVID-19 affected individuals.